The oral factor in adversarial civil proceedings - Hrabovska, Oksana O.; Zakharova, Olena S.; Priazhenkova, Nataliia O. (Linguistics and Culture Review, 2021)
The relevance of the problem stated in this paper is conditioned by the fact that under any circumstances the parties are carriers of certain evidentiary information about facts and their explanations are evidence. The explanations of the parties provide the court with important material for proving and making a decision on the case. This is ensured by the oral nature of civil proceedings since civil cases are usually considered orally in courts. The purpose of the paper is to establish the degree of application of the oral factor in adversarial civil proceedings. An analytical method was used as one of the main ones, which made it possible to assess the oral factor in civil proceedings from the ancient times of its initial introduction to the present.